EXPLORING THE EFFICACY OF 360-DEGREE PERFORMANCE APPRAISAL SYSTEMS IN INFORMATION TECHNOLOGY INDUSTRIES - Renjitha S. V; Priya K (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the rapidly evolving landscape of Information Technology (IT) industries, the traditional top-down performance appraisal systems often struggle to capture the nuanced contributions and dynamics of modern workplace environments. The study intends to analyze the entire influence of multi-rater feedback systems on employee performance, organizational culture, and overall productivity. It will consider feedback from supervisors, peers, subordinates, and clients to gain a thorough understanding of the effects. The research aims to uncover the complexities of adopting 360-degree assessment in IT environments. It will explore the benefits, obstacles, and best practices associated with this appraisal approach. This study aims to provide practical insights for HR practitioners, managers, and organizational leaders in the IT industry who are looking to improve performance evaluation processes. It focuses on the specific challenges and concerns of establishing 360-degree appraisal systems in this dynamic sector.